Objective scoring of streetscape walkability related to leisure walking: Statistical modeling approach with semantic segmentation of Google Street View images. (November 2020) - Nagata, Shohei; Nakaya, Tomoki; Hanibuchi, Tomoya; Amagasa, Shiho; Kikuchi, Hiroyuki; Inoue, Shigeru
Abstract: Although the pedestrian-friendly qualities of streetscapes promote walking, quantitative understanding of streetscape functionality remains insufficient. This study proposed a novel automated method to assess streetscape walkability (SW) using semantic segmentation and statistical modeling on Google Street View images. Using compositions of segmented streetscape elements, such as buildings and street trees, a regression-style model was built to predict SW, scored using a human-based auditing method. Older female active leisure walkers living in Bunkyo Ward, Tokyo, are associated with SW scores estimated by the model (OR = 3.783; 95% CI = 1.459 to 10.409), but male walkers are not. Highlights: Semantic segmentation method enabled quantification of streetscapes. Several segmented components were related to streetscape walkability (SW). Automatic evaluation of SW produced association with older females leisure walking.